Особливості проведення маркетингових досліджень конкурентного середовища підприємства - Ларка, Людмила Сергіївна; Жабська, О. В. (НТУ "ХПІ", 2015)
В статті пропонується систематизація вхідної інформації в залежності від мети дослідження конкурентного середовища. Обґрунтована доцільність складання карти стратегічних групконкурентів для аналізу їх конкурентних стратегій. Розглянуті можливі стратегічні групи конкурентів та очікувані від них конкурентні стратегії. Сформульовані основні складові конкурентоспроможності підприємства з позиції раціонального управління його потенціалом.

Relevance of the study of the competitive environment due to the need to systematize the flow of incoming information for the analysis of competitive forces, identify strategic groups of competitors. The purpose of the article is to offer methodological tools to improve the quality of organization studies the competitive environment of the enterprise. The paper proposes the systematization of incoming information depending on the purpose of the study of the competitive environment. Expediency mapping strategic groups of competitors to analyze their competitive strategies is given. The possible strategic groups of competitors and their expected competitive strategies are shown. The basic components of the competitiveness of the enterprise from the perspective of rational management of its potential are given. To construct the maps of strategic groups of competitors are encouraged to apply the following characteristics: market share and refresh rates range of products. These figures reflect the effectiveness of the marketing strategies of enterprises and their innovative activity. Prospects for further studies of the competitive environment of the enterprise are to empower the purposes of research and improvement of the list of information for each study.
Features of the marketing research of the enterprise competitive environment
Keywords: конкурентоспроможність підприємства; конкурентні переваги; карта стратегічних груп; стратегічне управління; enterprise competitiveness; competitive advantages; market conditions; strategic management; information flows